A method for preparing polypropylene film for current collector negative electrode material composite copper foil

By modifying nanofillers and modified polypropylene films with PVDF and acrylate copolymers, combined with a synchronous bidirectional stretching process, the problem of insufficient binding force between copper foil and active substances is solved, and the performance and life of the battery are improved.

CN119735842AInactive Publication Date: 2025-04-01ZHEJIANG NANYANG HUACHENG TECH CO LTD
View PDF 0 Cites 3 Cited by

Patent Information

Application Number
CN202510245189.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-03-04
Publication Date
2025-04-01
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

In traditional lithium battery current collector negative electrode materials, the bonding force between the copper foil and the active substance is weak, causing the active substance to fall off and affect the battery performance and life.

Method used

Modified nanofillers and PVDF and a small amount of acrylate copolymer are used to improve the mechanical properties of the film and the adhesion strength of the copper foil through a synchronous bidirectional stretching process.

Benefits of technology

The bonding strength between polypropylene film and copper foil is improved, the mechanical properties and electrical breakdown resistance of the film are enhanced, and the service life of the battery is extended.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The invention discloses a method for preparing a polypropylene film for a current collector negative electrode material composite copper foil, which belongs to the field of polymer materials. The modified nanofiller is prepared and added, and polypropylene is modified by combining PVDF and a small amount of acrylic copolymer, and a modified polypropylene crude film is obtained under a synchronous stretching process, and further heat treatment and corona treatment are performed to obtain a polypropylene film for a current collector negative electrode material composite copper foil. The scheme improves the orientation arrangement of molecular chains in the film stretching process by modifying the nanofiller, enhances the mechanical properties of the polypropylene film, has better anti-electrical breakdown performance, and at the same time serves as an anchor point for copper foil adsorption, thereby improving the copper foil adsorption capacity.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of polymer materials, and in particular to a method for preparing a polypropylene film for a current collector negative electrode material composite copper foil. Background Art

[0002] The current collector negative electrode material plays a vital role in lithium-ion batteries. Traditional current collector negative electrode materials mostly use copper foil. However, copper foil has some shortcomings during use, such as weak binding force with active substances, which easily causes active substances to fall off, thus affecting the performance and life of the battery. Composite copper foil refers to a sandwich structure composite material formed by copper plating on the surface of a plastic film, which is used to replace traditional lithium battery copper foil. As the negative electrode current collector of lithium batteries, composite copper foil has advantages over traditional lithium battery copper foil in terms of energy density, safety and cost.

[0003] The core production process of composite copper foil is to realize the conductivity and metallization of the film on substrates such as PET, PP, and PI through vacuum coating technology, thereby forming a thin layer of copper metal coating. Subsequently, the copper coating is thickened by traditional water-based electroplating technology. The two-step method is the mainstream technology currently widely used. The process includes two stages: magnetron sputtering and water electroplating thickening, which requires magnetron sputtering equipment and water electroplating equipment. Some manufacturers have also proposed other methods, such as the one-step method, which is divided into two types: chemical and physical, and both are one-time molding; the three-step method includes three steps: magnetron sputtering, vacuum evaporation, and water electroplating. After magnetron sputtering, a vacuum evaporation step is added, so additional vacuum evaporation equipment is required.

[0004] However, PP film cannot resist long-term exposure to ultraviolet rays and heat energy from sunlight. It is easily aged and cracked by light, heat and oxygen. It cannot withstand low temperature environments, and its bonding strength with copper foil needs to be improved. In the prior art, CN115340725 B discloses a high tensile strength polypropylene film for lithium battery current collector and its preparation method. Carboxylated polypyrrole is obtained by amino protection, acylation, bromoform reaction and deprotection of polypyrrole, and then the carboxylated polypyrrole is immersed in an alkaline solution to finally obtain modified polypyrrole. The modified polypyrrole is used to modify polypropylene to obtain a polypropylene film, which improves the low-temperature brittleness and low impact resistance of the polypropylene film. However, it does not improve the bonding performance of the polypropylene film for composite copper foil and copper foil. Summary of the invention

[0005] To solve the above problems, the present invention provides a method for preparing a polypropylene film for a current collector negative electrode material composite copper foil. The prepared polypropylene film has a high bonding strength with the copper foil, the production process is simple, and can be matched with existing equipment.

[0006] To achieve the above object, the technical solution of the present invention is: This scheme proposes a method for preparing a polypropylene film for a current collector negative electrode material composite copper foil, comprising the following steps: Step (1): by weight, 3 to 5 parts of an acrylic acid ester monomer, 10 to 15 parts of a vinylidene fluoride monomer, and 5 to 8 parts of a modified nanofiller are mixed uniformly, and then 0.1 to 0.3 parts of an initiator are added under a nitrogen atmosphere at 65 to 85° C., and the mixture is stirred and copolymerized to obtain component A; Step (2): by weight, 3 to 5 parts of component A and 10 to 20 parts of PVDF are mixed and stirred at 180°C to 220°C under nitrogen for 60 to 120 minutes, and then cooled and granulated to obtain component B; Step (3): by weight, 1 to 5 parts of component B are mixed with 10 to 20 parts of polypropylene, melt-extruded and then cast, and then cut through a cooling roller to form a cast sheet, and then synchronously stretched to obtain a rough film; The process parameters of the synchronous stretching are: longitudinal stretching temperature 125°C-145°C, stretching ratio 4.5-6.0; transverse stretching temperature 150°C-160°C, stretching ratio 8.0-10.0; Step (4): heat-treating and corona-treating the crude film and then rolling it up to obtain a polypropylene film; The preparation method of the modified nanofiller comprises the following steps: (1-1) Disperse 10 to 20 parts of nanofiller powder in an equal weight of water, add 0.1 to 0.5 parts of silane coupling agent, and ball mill for 30 to 40 minutes to obtain a slurry; (1-2) By weight, 5 to 10 parts of vinylidene fluoride monomer are added to 10 to 20 parts of the slurry, followed by grinding in a sand mill for 30 to 60 minutes and concentrating until the water content is less than 2% to obtain a modified nanofiller.

[0007] This solution has the following features: 1. Prepare and add modified nanofillers, which can be evenly dispersed in polypropylene film. Traditional nanofillers are difficult to disperse well in organic films. In this scheme, traditional nanofillers are modified, that is, silane coupling agents are grafted on their surfaces through ball milling, and further grafted with vinylidene fluoride monomers through sand milling, so that they can be fully dispersed in step (1).

[0008] Modified nanofillers can enhance the mechanical properties of polypropylene film. In step (1), after the acrylate monomer and the vinylidene fluoride monomer are blended, an initiator is added, and the polymerization reaction first occurs on the surface of the modified nanofiller, which is beneficial to the orientation arrangement of the molecular chain during the stretching process, improves the crystallinity, and has better resistance to electrical breakdown. In addition, the filler metal elements partially exposed on the surface of the polypropylene film can form anchor points during the subsequent composite copper foil, thereby enhancing the adsorption strength of the copper foil. The addition of traditional nanofillers will reduce the crystallinity of PVDF. This is because traditional nanofillers break the local regular arrangement of PVDF. When stretched, traditional nanofillers will not drive the molecular chains of PVDF to rotate, so they cannot improve the crystallinity.

[0009] 2. Modify polypropylene through PVDF and a small amount of acrylic copolymer. Polypropylene film cannot resist long-term exposure to ultraviolet rays and heat energy from sunlight. It is easily aged and cracked by light, heat and oxygen. It cannot withstand low temperature environments. PVDF has excellent mechanical properties, thermal stability and chemical stability, and is easy to form films. However, the adhesion between PVDF and polypropylene resin is poor. The introduction of acrylic monomers can improve the adhesion between PVDF and polypropylene resin, and improve the elongation at break of the finished film, avoiding the premature penetration of fine fly marks induced during the stress process of the film into large cracks.

[0010] 3. Adjust the longitudinal and transverse stretching multiples of synchronous stretching to obtain the longitudinal and transverse tensile strengths to be achieved by the polypropylene film for current collector. The film-forming property of asynchronous production line is poor, and there are problems such as uneven film thickness, bubbles, and breakage, which affect the quality and performance of the film. In addition, the process parameters of synchronous stretching are related to the amount of component B added. When the amount of component B added is large, the transverse stretching multiple can be slightly larger. During the stretching process of the film by synchronous biaxial stretching, the surface of the film does not need to contact any equipment, so there will be no defects such as scratches and bumps on the surface of the film, which greatly improves the surface quality of the synchronous biaxially stretched film. During the stretching process of the film by synchronous biaxial stretching, since the two sides of the film are clamped by the chain clamps, the film will not shrink on the sides during the stretching orientation process of the film, which improves the uniformity of the film thickness.

[0011] Preferably, in step (1), the initiator is azobisisobutyronitrile; and the acrylic ester monomer is one of methyl acrylate, ethyl acrylate, 2-methyl methacrylate and 2-ethyl methacrylate.

[0012] Preferably, in step (1-1), the nano filler powder is one or more of nano silicon dioxide, nano calcium carbonate, nano titanium dioxide, nano magnesium oxide, and nano zinc oxide.

[0013] Preferably, in step (1-2), the silane coupling agent is one of aminosilane, epoxysilane, thiosilane, methacryloxysilane, vinylsilane, ureasilane and isocyanatesilane.

[0014] Preferably, in step (1-2), the grinding speed in the sand mill is 1200 r / min~1500 r / min.

[0015] Preferably, in step (1-2), the water content of the modified nanofiller is less than 1%.

[0016] The water content of the modified nanofiller cannot be too high, as it will lead to the generation of water vapor in the subsequent process and affect product performance.

[0017] Preferably, in step (2), the mixing and stirring conditions are 800 r / min to 1000 r / min.

[0018] Preferably, in step (3), the temperature of the melt extrusion is 250°C~270°C, the temperature of the casting is 200°C~220°C, and the temperature of the cooling roller is 35°C~60°C; the thickness of the rough film is 3μm~6μm; and the process parameters of the synchronous stretching are: longitudinal stretching temperature 125°C~145°C, stretching ratio 5~5.5; transverse stretching temperature 150°C~160°C, stretching ratio 8.5~9.0.

[0019] Preferably, in step (4), the heat treatment process is as follows: in the first stage, the gas pressure is 0.05MPa-0.08MPa, and the temperature is kept at 170℃-180℃ for 10s-30s, resulting in 2%-5% relaxation in the horizontal direction; in the second stage, the temperature is kept at 140℃-150℃ for 3min-5min under ambient pressure conditions, resulting in 5%-10% relaxation in the horizontal direction; the corona treatment process is as follows: the strength of the electrode during corona is 20W·min / m 2 ~25W·min / m 2 .

[0020] The first stage of heat treatment is carried out at a high temperature and under negative pressure. This is to eliminate the air in the rough film and allow the air to overflow to the surface, while making the surface rough to improve the bonding strength with the copper foil; and to bridge the internal defects of the rough film layer and improve the mechanical strength of the film.

[0021] Compared with the prior art, the present invention has the following advantages: 1. This scheme improves the orientation arrangement of molecular chains during the film stretching process by modifying nanofillers, thereby enhancing the mechanical properties of polypropylene film, improving the crystallinity of the film after stretching, and having better resistance to electrical breakdown. At the same time, it serves as an anchor point for copper foil adsorption to improve the adsorption capacity of copper foil.

[0022] 2. This scheme improves the weather resistance of polypropylene film by modifying polypropylene through PVDF and a small amount of acrylic copolymer. At the same time, the adhesion between PVDF and polypropylene resin is improved through acrylic esters, and a longer elongation at break of the PVDF film is maintained to prevent the fine fly marks induced during the stress process of the film from prematurely penetrating into large cracks; the longitudinal and transverse tensile strengths required for the polypropylene film for the current collector are obtained by adjusting the simultaneous longitudinal and transverse stretching multiples. DETAILED DESCRIPTION

[0023] The following is a description of the implementation of the present invention by specific embodiments. People familiar with the art can easily understand other advantages and effects of the present invention from the contents disclosed in this specification. Obviously, the described embodiments are part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0024] Embodiment 1 A method for preparing a polypropylene film for a current collector negative electrode material composite copper foil comprises the following steps: Step (1): by weight, 4 parts of 2-ethyl methacrylate monomer, 13 parts of vinylidene fluoride monomer, and 6 parts of modified nanofiller are mixed evenly, and then 0.2 parts of azobisisobutyronitrile is added under a nitrogen atmosphere at 75° C., and the mixture is stirred and copolymerized to obtain component A; Step (2): by weight, 4 parts of component A and 15 parts of PVDF were mixed and stirred at 900 r / min for 90 minutes under nitrogen conditions at 200°C, and then cooled and granulated to obtain component B; Step (3): by weight, 3 parts of component B and 15 parts of polypropylene are mixed, melt extruded and then cast, and then cut through a cooling roller to form a cast sheet, and then stretched synchronously to obtain a rough film; the temperature of the melt extrusion is 260°C, the temperature of the casting is 210°C, and the temperature of the cooling roller is 40°C; the thickness of the rough film is 4 μm; The process parameters of synchronous stretching are: longitudinal stretching temperature 135°C, stretching ratio 5; transverse stretching temperature 150°C, stretching ratio 10.0; Step (4): The crude film is subjected to heat treatment and corona treatment and then rolled up to obtain a polypropylene film; the heat treatment process is as follows: in the first stage, the air pressure is 0.06 MPa, and the temperature is kept at 180°C for 20 seconds, resulting in 3% relaxation in the transverse direction; in the second stage, the temperature is kept at 145°C for 4 minutes under ambient air pressure conditions, resulting in 7% relaxation in the transverse direction; the corona treatment process is as follows: the strength of the electrode during corona is 22 W·min / m 2 ; The preparation method of the modified nanofiller comprises the following steps: (1-1) Disperse 5 parts of nano-silicon dioxide, 5 parts of nano-calcium carbonate, 5 parts of nano-magnesium oxide, and 5 parts of nano-zinc oxide in equal parts of water, add 0.3 parts of vinyl silane, and ball-mill for 30 minutes to obtain a slurry; (1-2) By weight, 8 parts of vinylidene fluoride monomer were added to 15 parts of the slurry, followed by grinding in a sand mill at 1300 r / min for 50 min and concentrating until the water content was less than 1% to obtain a modified nanofiller.

[0025] Embodiment 2 A method for preparing a polypropylene film for a current collector negative electrode material composite copper foil comprises the following steps: Step (1): by weight, 5 parts of ethyl acrylate, 10 parts of vinylidene fluoride monomer, and 5 parts of modified nanofiller are mixed uniformly, and then 0.1 parts of azobisisobutyronitrile is added under a nitrogen atmosphere at 80° C., and the mixture is stirred and copolymerized to obtain component A; Step (2): by weight, 3 parts of component A and 10 parts of PVDF were mixed and stirred at 800 r / min for 60 min under nitrogen conditions at 180°C, and then cooled and granulated to obtain component B; Step (3): by weight, 1 part of component B is mixed with 10 parts of polypropylene, melt-extruded and then cast, and cut through a cooling roller to form a cast sheet, and then stretched synchronously to obtain a rough film; the temperature of the melt extrusion is 250°C, the temperature of the casting is 200°C, and the temperature of the cooling roller is 35°C; the thickness of the rough film is 4 μm; The process parameters of synchronous stretching are: longitudinal stretching temperature 135°C, stretching ratio 5.0; transverse stretching temperature 150°C, stretching ratio 8.0; Step (4): The crude film is subjected to heat treatment and corona treatment and then rolled up to obtain a polypropylene film; the heat treatment process is as follows: in the first stage, the air pressure is 0.05 MPa, and the temperature is kept at 170°C for 30 seconds, resulting in 2% relaxation in the transverse direction; in the second stage, the temperature is kept at 150°C for 3 minutes under ambient air pressure conditions, resulting in 5% relaxation in the transverse direction; the corona treatment process is as follows: the strength of the electrode during corona is 20 W·min / m 2 ; The preparation method of the modified nanofiller comprises the following steps: (1-1) Disperse 5 parts of nano-silicon dioxide, 5 parts of nano-calcium carbonate, and 5 parts of nano-titanium dioxide in equal parts of water, add 0.2 parts of aminosilane, and ball-mill for 30 minutes to obtain a slurry; (1-2) 5 parts of vinylidene fluoride monomer were added to 10 parts of the slurry by weight, and then introduced into a sand mill for grinding at 1200 r / min for 30 minutes. The mixture was concentrated at 60° C. until the water content was less than 1% to obtain a modified nanofiller.

[0026] Embodiment 3 A method for preparing a polypropylene film for a current collector negative electrode material composite copper foil comprises the following steps: Step (1): by weight, 5 parts of methyl acrylate monomer, 15 parts of vinylidene fluoride monomer, and 8 parts of modified nanofiller are mixed uniformly, and then 0.3 parts of azobisisobutyronitrile is added under a nitrogen atmosphere at 85° C., and the mixture is stirred and copolymerized to obtain component A; Step (2): by weight, 5 parts of component A and 20 parts of PVDF were mixed and stirred at 1000 r / min for 120 min under nitrogen conditions at 220°C, and then cooled and granulated to obtain component B; Step (3): by weight, 5 parts of component B are mixed with 20 parts of polypropylene, melt extruded and then cast, and cut through a cooling roller to form a cast sheet, and then stretched synchronously to obtain a rough film; the temperature of the melt extrusion is 270°C, the temperature of the casting is 220°C, and the temperature of the cooling roller is 60°C; the thickness of the rough film is 6 μm; The process parameters of synchronous stretching are: longitudinal stretching temperature 145℃, stretching ratio 6.0; transverse stretching temperature 150℃~160℃, stretching ratio 9.0; Step (4): The crude film is subjected to heat treatment and corona treatment and then rolled up to obtain a polypropylene film; the heat treatment process is as follows: in the first stage, the air pressure is 0.08 MPa, the temperature is kept at 180°C for 10 seconds, and 5% relaxation is generated in the transverse direction; in the second stage, the temperature is kept at 150°C for 3 minutes under ambient air pressure conditions, and 5% relaxation is generated in the transverse direction; the corona treatment process is as follows: the strength of the electrode during corona is 25 W·min / m 2 ; The preparation method of the modified nanofiller comprises the following steps: (1-1) Disperse 5 parts of nano silicon dioxide, 5 parts of nano titanium dioxide, and 5 parts of nano zinc oxide in equal parts of water, add 0.5 parts of methacryloxysilane, and ball-mill for 40 minutes to obtain a slurry; (1-2) 10 parts by weight of vinylidene fluoride monomer were added to 20 parts by weight of the slurry, followed by grinding in a sand mill at 1500 r / min for 60 min and concentrating the slurry until the water content was less than 2% to obtain a modified nanofiller.

[0027] Embodiment 4 A method for preparing a polypropylene film for a current collector negative electrode material composite copper foil comprises the following steps: Step (1): by weight, 4 parts of 2-ethyl methacrylate monomer, 13 parts of vinylidene fluoride monomer, and 6 parts of modified nanofiller are mixed evenly, and then 0.2 parts of azobisisobutyronitrile is added under a nitrogen atmosphere at 75° C., and the mixture is stirred and copolymerized to obtain component A; Step (2): by weight, 4 parts of component A and 15 parts of PVDF were mixed and stirred at 900 r / min for 90 minutes under nitrogen conditions at 200°C, and then cooled and granulated to obtain component B; Step (3): by weight, 3 parts of component B and 15 parts of polypropylene are mixed, melt extruded and then cast, and then cut through a cooling roller to form a cast sheet, and then stretched synchronously to obtain a rough film; the temperature of the melt extrusion is 260°C, the temperature of the casting is 210°C, and the temperature of the cooling roller is 40°C; the thickness of the rough film is 4 μm; The process parameters of synchronous stretching are: longitudinal stretching temperature 135°C, stretching ratio 6; transverse stretching temperature 150°C, stretching ratio 9.0; Step (4): The crude film is subjected to heat treatment and corona treatment and then rolled up to obtain a polypropylene film; the heat treatment process is as follows: in the first stage, the air pressure is 0.06 MPa, and the temperature is kept at 180°C for 20 seconds, resulting in 3% relaxation in the transverse direction; in the second stage, the temperature is kept at 145°C for 4 minutes under ambient air pressure conditions, resulting in 7% relaxation in the transverse direction; the corona treatment process is as follows: the strength of the electrode during corona is 22 W·min / m 2 ; The preparation method of the modified nanofiller comprises the following steps: (1-1) Disperse 5 parts of nano-silicon dioxide, 5 parts of nano-calcium carbonate, 5 parts of nano-magnesium oxide, and 5 parts of nano-zinc oxide in equal parts of water, add 0.3 parts of vinyl silane, and ball-mill for 30 minutes to obtain a slurry; (1-2) By weight, 8 parts of vinylidene fluoride monomer were added to 15 parts of the slurry, followed by grinding in a sand mill at 1300 r / min for 50 min and concentrating until the water content was less than 1% to obtain a modified nanofiller.

[0028] Comparative Example 1 A method for preparing a polypropylene film for a current collector negative electrode material composite copper foil comprises the following steps: Step (1): by weight, 4 parts of ethyl 2-methacrylate monomer, 13 parts of vinylidene fluoride monomer, and 6 parts of nanofiller are mixed evenly, and then 0.2 parts of azobisisobutyronitrile is added under a nitrogen atmosphere at 75° C., and the mixture is stirred and copolymerized to obtain component A; Step (2): by weight, 4 parts of component A and 15 parts of PVDF were mixed and stirred at 900 r / min for 90 minutes under nitrogen conditions at 200°C, and then cooled and granulated to obtain component B; Step (3): by weight, 3 parts of component B and 15 parts of polypropylene are mixed, melt extruded and then cast, and then cut through a cooling roller to form a cast sheet, and then stretched synchronously to obtain a rough film; the temperature of the melt extrusion is 260°C, the temperature of the casting is 210°C, and the temperature of the cooling roller is 40°C; the thickness of the rough film is 4 μm; The process parameters of synchronous stretching are: longitudinal stretching temperature 135°C, stretching ratio 5; transverse stretching temperature 150°C, stretching ratio 10.0; Step (4): The crude film is subjected to heat treatment and corona treatment and then rolled up to obtain a polypropylene film; the heat treatment process is as follows: in the first stage, the air pressure is 0.06 MPa, and the temperature is kept at 180°C for 20 seconds, resulting in 3% relaxation in the transverse direction; in the second stage, the temperature is kept at 145°C for 4 minutes under ambient air pressure conditions, resulting in 7% relaxation in the transverse direction; the corona treatment process is as follows: the strength of the electrode during corona is 22 W·min / m 2 .

[0029] Comparative Example 2 A method for preparing a polypropylene film for a current collector negative electrode material composite copper foil comprises the following steps: Step (1): 4 parts by mass of ethyl 2-methacrylate monomer and 13 parts by mass of vinylidene fluoride monomer are mixed evenly, and then 0.2 parts of azobisisobutyronitrile is added under a nitrogen atmosphere at 75° C., and the mixture is stirred and copolymerized, and then 6 parts of modified nanofiller are added to obtain component A; Step (2): by weight, 4 parts of component A and 15 parts of PVDF were mixed and stirred at 900 r / min for 90 minutes under nitrogen conditions at 200°C, and then cooled and granulated to obtain component B; Step (3): by weight, 3 parts of component B and 15 parts of polypropylene are mixed, melt extruded and then cast, and then cut through a cooling roller to form a cast sheet, and then stretched synchronously to obtain a rough film; the temperature of the melt extrusion is 260°C, the temperature of the casting is 210°C, and the temperature of the cooling roller is 40°C; the thickness of the rough film is 4 μm; The process parameters of synchronous stretching are: longitudinal stretching temperature 135°C, stretching ratio 5; transverse stretching temperature 150°C, stretching ratio 10.0; Step (4): The crude film is subjected to heat treatment and corona treatment and then rolled up to obtain a polypropylene film; the heat treatment process is as follows: in the first stage, the air pressure is 0.06 MPa, and the temperature is kept at 180°C for 20 seconds, resulting in 3% relaxation in the transverse direction; in the second stage, the temperature is kept at 145°C for 4 minutes under ambient air pressure conditions, resulting in 7% relaxation in the transverse direction; the corona treatment process is as follows: the strength of the electrode during corona is 22 W·min / m 2 ; The preparation method of the modified nanofiller comprises the following steps: (1-1) Disperse 5 parts of nano-silicon dioxide, 5 parts of nano-calcium carbonate, 5 parts of nano-magnesium oxide, and 5 parts of nano-zinc oxide in equal parts of water, add 0.3 parts of vinyl silane, and ball-mill for 30 minutes to obtain a slurry; (1-2) By weight, 8 parts of vinylidene fluoride monomer were added to 15 parts of the slurry, followed by grinding in a sand mill at 1300 r / min for 50 min and concentrating until the water content was less than 1% to obtain a modified nanofiller.

[0030] Comparative Example 3 A method for preparing a polypropylene film for a current collector negative electrode material composite copper foil comprises the following steps: Step (1): 3 parts of PVDF and 15 parts of polypropylene are mixed by weight, melt extruded and then cast, and then cut through a cooling roller to form a cast sheet, and then stretched synchronously to obtain a rough film; the temperature of the melt extrusion is 260°C, the temperature of the casting is 210°C, and the temperature of the cooling roller is 40°C; the thickness of the rough film is 4 μm; The process parameters of synchronous stretching are: longitudinal stretching temperature 135°C, stretching ratio 5; transverse stretching temperature 150°C, stretching ratio 10.0; Step (2): The crude film is subjected to heat treatment and corona treatment and then rolled up to obtain a polypropylene film; the heat treatment process is as follows: in the first stage, the air pressure is 0.06 MPa, and the temperature is kept at 180°C for 20 seconds, resulting in 3% relaxation in the transverse direction; in the second stage, the temperature is kept at 145°C for 4 minutes under ambient air pressure conditions, resulting in 7% relaxation in the transverse direction; the corona treatment process is as follows: the strength of the electrode during corona is 22 W·min / m 2 .

[0031] Comparative Example 4 A method for preparing a polypropylene film for a current collector negative electrode material composite copper foil comprises the following steps: Step (1): by weight, 4 parts of 2-ethyl methacrylate monomer, 13 parts of vinylidene fluoride monomer, and 6 parts of modified nanofiller are mixed evenly, and then 0.2 parts of azobisisobutyronitrile is added under a nitrogen atmosphere at 75° C., and the mixture is stirred and copolymerized to obtain component A; Step (2): by weight, 4 parts of component A and 15 parts of PVDF were mixed and stirred at 900 r / min for 90 minutes under nitrogen conditions at 200°C, and then cooled and granulated to obtain component B; Step (3): by weight, 3 parts of component B and 15 parts of polypropylene are mixed, melt extruded and then cast, and cut through a cooling roller to form a cast sheet, and then asynchronously stretched to obtain a crude film; the temperature of the melt extrusion is 260°C, the temperature of the casting is 210°C, and the temperature of the cooling roller is 40°C; the thickness of the crude film is 4 μm; The process parameters of asynchronous stretching are: longitudinal stretching temperature 135°C, stretching ratio 5; transverse stretching temperature 150°C, stretching ratio 10.0; Step (4): The crude film is subjected to heat treatment and corona treatment and then rolled up to obtain a polypropylene film; the heat treatment process is as follows: in the first stage, the air pressure is 0.06 MPa, and the temperature is kept at 180°C for 20 seconds, resulting in 3% relaxation in the transverse direction; in the second stage, the temperature is kept at 145°C for 4 minutes under ambient air pressure conditions, resulting in 7% relaxation in the transverse direction; the corona treatment process is as follows: the strength of the electrode during corona is 22 W·min / m 2 ; The preparation method of the modified nanofiller comprises the following steps: (1-1) Disperse 5 parts of nano-silicon dioxide, 5 parts of nano-calcium carbonate, 5 parts of nano-magnesium oxide, and 5 parts of nano-zinc oxide in equal parts of water, add 0.3 parts of vinyl silane, and ball-mill for 30 minutes to obtain a slurry; (1-2) By weight, 8 parts of vinylidene fluoride monomer were added to 15 parts of the slurry, followed by grinding in a sand mill at 1300 r / min for 50 min and concentrating until the water content was less than 1% to obtain a modified nanofiller.

[0032] Comparative Example 5 A method for preparing a polypropylene film for a current collector negative electrode material composite copper foil comprises the following steps: Step (1): by weight, 4 parts of 2-ethyl methacrylate monomer, 13 parts of vinylidene fluoride monomer, and 6 parts of modified nanofiller are mixed evenly, and then 0.2 parts of azobisisobutyronitrile is added under a nitrogen atmosphere at 75° C., and the mixture is stirred and copolymerized to obtain component A; Step (2): by weight, 4 parts of component A and 15 parts of PVDF were mixed and stirred at 900 r / min for 90 minutes under nitrogen conditions at 200°C, and then cooled and granulated to obtain component B; Step (3): by weight, 3 parts of component B and 15 parts of polypropylene are mixed, melt extruded and then cast, and then cut through a cooling roller to form a cast sheet, and then stretched synchronously to obtain a rough film; the temperature of the melt extrusion is 260°C, the temperature of the casting is 210°C, and the temperature of the cooling roller is 40°C; the thickness of the rough film is 4 μm; The process parameters of synchronous stretching are: longitudinal stretching temperature 135°C, stretching ratio 5; transverse stretching temperature 150°C, stretching ratio 10.0; Step (4): The crude film is subjected to heat treatment and corona treatment and then rolled up to obtain a polypropylene film; the heat treatment process is as follows: in the first stage, the air pressure is 0.06 MPa, and the temperature is kept at 180°C for 20 seconds, resulting in 3% relaxation in the transverse direction; in the second stage, the temperature is kept at 145°C for 4 minutes under ambient air pressure conditions, resulting in 7% relaxation in the transverse direction; the corona treatment process is as follows: the strength of the electrode during corona is 22 W·min / m 2 ; The preparation method of the modified nanofiller comprises the following steps: (1-1) Disperse 5 parts of nano-silicon dioxide, 5 parts of nano-calcium carbonate, 5 parts of nano-magnesium oxide, and 5 parts of nano-zinc oxide in equal parts of water, add 0.3 parts of vinyl silane, and ball-mill for 30 minutes to obtain a slurry; (1-2) 8 parts of vinylidene fluoride monomer were added to 15 parts of the slurry by weight, and then introduced into a sand mill and ground for 50 minutes at 1300 r / min. The slurry was concentrated to a water content of 2.5% to obtain a modified nanofiller.

[0033] Comparative Example 6 A method for preparing a polypropylene film for a current collector negative electrode material composite copper foil comprises the following steps: Step (1): 13 parts by weight of vinylidene fluoride monomer and 6 parts of modified nanofiller are mixed evenly, and then 0.2 parts of azobisisobutyronitrile are added under a nitrogen atmosphere at 75° C., and the mixture is stirred and copolymerized to obtain component A; Step (2): by weight, 4 parts of component A and 15 parts of PVDF were mixed and stirred at 900 r / min for 90 minutes under nitrogen conditions at 200°C, and then cooled and granulated to obtain component B; Step (3): by weight, 3 parts of component B and 15 parts of polypropylene are mixed, melt extruded and then cast, and then cut through a cooling roller to form a cast sheet, and then stretched synchronously to obtain a rough film; the temperature of the melt extrusion is 260°C, the temperature of the casting is 210°C, and the temperature of the cooling roller is 40°C; the thickness of the rough film is 4 μm; The process parameters of synchronous stretching are: longitudinal stretching temperature 135°C, stretching ratio 5; transverse stretching temperature 150°C, stretching ratio 10.0; Step (4): The crude film is subjected to heat treatment and corona treatment and then rolled up to obtain a polypropylene film; the heat treatment process is as follows: in the first stage, the air pressure is 0.06 MPa, and the temperature is kept at 180°C for 20 seconds, resulting in 3% relaxation in the transverse direction; in the second stage, the temperature is kept at 145°C for 4 minutes under ambient air pressure conditions, resulting in 7% relaxation in the transverse direction; the corona treatment process is as follows: the strength of the electrode during corona is 22 W·min / m 2 ; The preparation method of the modified nanofiller comprises the following steps: (1-1) Disperse 5 parts of nano-silicon dioxide, 5 parts of nano-calcium carbonate, 5 parts of nano-magnesium oxide, and 5 parts of nano-zinc oxide in equal parts of water, add 0.3 parts of vinyl silane, and ball-mill for 30 minutes to obtain a slurry; (1-2) By weight, 8 parts of vinylidene fluoride monomer were added to 15 parts of the slurry, followed by grinding in a sand mill at 1300 r / min for 50 min and concentrating until the water content was less than 1% to obtain a modified nanofiller.

[0034] Comparative Example 7 A method for preparing a polypropylene film for a current collector negative electrode material composite copper foil comprises the following steps: Step (1): by weight, 4 parts of 2-ethyl methacrylate monomer, 13 parts of vinylidene fluoride monomer, and 6 parts of modified nanofiller are mixed evenly, and then 0.2 parts of azobisisobutyronitrile is added under a nitrogen atmosphere at 75° C., and the mixture is stirred and copolymerized to obtain component A; Step (2): by weight, 4 parts of component A and 15 parts of PVDF were mixed and stirred at 900 r / min for 90 minutes under nitrogen conditions at 200°C, and then cooled and granulated to obtain component B; Step (3): by weight, 3 parts of component B and 15 parts of polypropylene are mixed, melt extruded and then cast, and then cut through a cooling roller to form a cast sheet, and then stretched synchronously to obtain a rough film; the temperature of the melt extrusion is 260°C, the temperature of the casting is 210°C, and the temperature of the cooling roller is 40°C; the thickness of the rough film is 4 μm; The process parameters of synchronous stretching are: longitudinal stretching temperature 135°C, stretching ratio 5; transverse stretching temperature 150°C, stretching ratio 10.0; Step (4): The crude film is subjected to heat treatment and corona treatment and then rolled up to obtain a polypropylene film; the heat treatment process is as follows: in the first stage, under ambient pressure conditions, the film is kept at 180°C for 20 seconds, resulting in 3% relaxation in the transverse direction; in the second stage, under ambient pressure conditions, the film is kept at 145°C for 4 minutes, resulting in 7% relaxation in the transverse direction; the corona treatment process is as follows: the strength of the electrode during corona treatment is 22 W·min / m 2 ; The preparation method of the modified nanofiller comprises the following steps: (1-1) Disperse 5 parts of nano-silicon dioxide, 5 parts of nano-calcium carbonate, 5 parts of nano-magnesium oxide, and 5 parts of nano-zinc oxide in equal parts of water, add 0.3 parts of vinyl silane, and ball-mill for 30 minutes to obtain a slurry; (1-2) By weight, 8 parts of vinylidene fluoride monomer were added to 15 parts of the slurry, followed by grinding in a sand mill at 1300 r / min for 50 min and concentrating until the water content was less than 1% to obtain a modified nanofiller.

[0035] Performance testing: 1. Refer to GB / T13542.2-2009 standard to characterize the polypropylene film; 2. The dielectric properties of polypropylene film are tested according to GB / T 1409-2006 test standard; 3. Test of the adhesion performance of copper foil on polypropylene film: first, copper is attached to the polypropylene film by evaporation, and then thickened by electroplating to obtain a copper foil layer with a thickness of 10μm. The surface state is observed under a 500x optical microscope and rated 0-4 levels according to the number of defects, with 0 being no defects.

[0036] The test results are shown in Table 1.

[0037] Table 1 It can be seen from the above results that the polypropylene films prepared in Examples 1 to 4 have better mechanical properties and electrical properties than the polypropylene films prepared in Comparative Examples 1 to 7.

[0038] The main difference between Comparative Example 1 and Example 1 is that ordinary nanofillers are added in Comparative Example 1. Ordinary nanofillers have dispersion problems during the preparation process. Although ordinary nanofillers can also serve as copolymerization sites, ordinary nanofillers will cause uneven distribution, which in turn causes uneven distribution of properties of the finished film, and ultimately leads to decreased mechanical and electrical properties. In addition, the uneven distribution of ordinary nanofillers will affect the uneven distribution of stress on the surface of the finished film, which will eventually lead to decreased adhesion of the copper foil, resulting in cracks, vacancies, microcracks, etc.

[0039] The main difference between Comparative Example 2 and Example 1 is that the modified nanofiller in Comparative Example 2 is added after the copolymerization reaction. This shows that the timing of adding the modified nanofiller in Example 1 is better, mainly because the modified nanofiller in Example 1 acts as a "nucleating agent" for the copolymerization reaction, making it more tightly bonded to the polymer. During the film stretching process, the polymer molecular chain moves with the modified nanofiller, thereby improving the crystallinity, while the modified nanofiller in Comparative Example 2 is added after the copolymerization reaction without such effect.

[0040] The main difference between Comparative Example 3 and Example 1 is that PVDF and polypropylene are directly co-extruded in Comparative Example 3. Since the bonding strength between PVDF and polypropylene is low, the mechanical and electrical properties of Comparative Example 3 are poor. The main difference between Comparative Example 6 and Example 1 is that no acrylic acid ester monomer is added, which makes its performance similar to that of Comparative Example 3.

[0041] The main difference between Comparative Example 4 and Example 1 is that asynchronous stretching is used in Comparative Example 4. Asynchronous stretching easily produces tiny fly marks, which leads to a decrease in mechanical strength and electrical properties after film formation, and easily causes micro cracks on the surface of the copper foil.

[0042] The main difference between Comparative Example 5 and Example 1 is that the water content in the modified filler is too high. The high water content in the modified filler may cause the polymer of Comparative Example 5 to undergo a certain degree of hydrolysis during the film preparation process, resulting in excessive surface roughness and decreased mechanical and electrical properties.

[0043] The main difference between Comparative Example 7 and Example 1 is that negative pressure treatment is not performed in the first stage of heat treatment, which makes it possible for trace gases in the film to not be removed, and easily become crack sources, resulting in decreased mechanical properties. At the same time, the surface roughness is low, which is not conducive to copper foil adsorption.

[0044] The above description is only a preferred specific implementation manner of the present invention, but the protection scope of the present invention is not limited thereto. Any technician familiar with the technical field can make equivalent replacements or changes according to the technical scheme and inventive concept of the present invention within the technical scope disclosed by the present invention, which should be covered by the protection scope of the present invention.

Claims

1. A method for preparing a polypropylene film for a current collector negative electrode material composite copper foil, characterized in that: The following steps are involved: Step (1): by weight, 3 to 5 parts of an acrylic acid ester monomer, 10 to 15 parts of a vinylidene fluoride monomer, and 5 to 8 parts of a modified nanofiller are mixed uniformly, and then 0.1 to 0.3 parts of an initiator are added under a nitrogen atmosphere at 65 to 85° C., and the mixture is stirred and copolymerized to obtain component A; Step (2): by weight, 3 to 5 parts of component A and 10 to 20 parts of PVDF are mixed and stirred at 180°C to 220°C under nitrogen for 60 to 120 minutes, and then cooled and granulated to obtain component B; Step (3): by weight, 1 to 5 parts of component B are mixed with 10 to 20 parts of polypropylene, melt-extruded and then cast, and then cut through a cooling roller to form a cast sheet, and then synchronously stretched to obtain a rough film; The process parameters of the synchronous stretching are: longitudinal stretching temperature 125°C-145°C, stretching ratio 4.5-6.0; transverse stretching temperature 150°C-160°C, stretching ratio 8.0-10.0; Step (4): heat-treating and corona-treating the crude film and then rolling it up to obtain a polypropylene film; The preparation method of the modified nanofiller comprises the following steps: (1-1) Disperse 10 to 20 parts of nanofiller powder in an equal weight of water, add 0.1 to 0.5 parts of silane coupling agent, and ball mill for 30 to 40 minutes to obtain a slurry; (1-2) By weight, 5 to 10 parts of vinylidene fluoride monomer are added to 10 to 20 parts of the slurry, followed by grinding in a sand mill for 30 to 60 minutes and concentrating until the water content is less than 2% to obtain a modified nanofiller.

2. The method for preparing a polypropylene film for a current collector negative electrode material composite copper foil according to claim 1, characterized in that: In step (1), the initiator is azobisisobutyronitrile; and the acrylic ester monomer is one of methyl acrylate, ethyl acrylate, 2-methyl methacrylate, and 2-ethyl methacrylate.

3. The method for preparing the polypropylene film for the current collector negative electrode material composite copper foil according to claim 1, characterized in that: In step (1-1), the nano filler powder is one or more of nano silicon dioxide, nano calcium carbonate, nano titanium dioxide, nano magnesium oxide, and nano zinc oxide.

4. The method for preparing the polypropylene film for the current collector negative electrode material composite copper foil according to claim 1, characterized in that: In step (1-2), the silane coupling agent is one of aminosilane, epoxysilane, thiosilane, methacryloxysilane, vinylsilane, ureasilane and isocyanatesilane.

5. The method for preparing the polypropylene film for the current collector negative electrode material composite copper foil according to claim 1, characterized in that: In step (1-2), the grinding speed in the sand mill is 1200 r / min~1500 r / min.

6. The method for preparing the polypropylene film for the current collector negative electrode material composite copper foil according to claim 1, characterized in that: In step (1-2), the water content of the modified nanofiller is less than 1%.

7. The method for preparing a polypropylene film for a current collector negative electrode material composite copper foil according to claim 1, characterized in that: In step (2), the mixing and stirring conditions are 800r / min~1000r / min.

8. The method for preparing a polypropylene film for a current collector negative electrode material composite copper foil according to claim 1, characterized in that: In step (3), the temperature of the melt extrusion is 250°C~270°C, the temperature of the casting is 200°C~220°C, and the temperature of the cooling roller is 35°C~60°C; the thickness of the rough film is 3μm~6μm; the process parameters of the synchronous stretching are: longitudinal stretching temperature 125°C~145°C, stretching ratio 5~5.5; transverse stretching temperature 150°C~160°C, stretching ratio 8.5~9.

0.

9. The method for preparing a polypropylene film for a current collector negative electrode material composite copper foil according to claim 1, characterized in that: In step (4), the heat treatment process is as follows: in the first stage, the pressure is 0.05MPa to 0.08MPa, and the temperature is kept at 170℃ to 180℃ for 10s to 30s, resulting in 2% to 5% relaxation in the horizontal direction; in the second stage, the temperature is kept at 140℃ to 150℃ for 3min to 5min under ambient pressure conditions, resulting in 5% to 10% relaxation in the horizontal direction; the corona treatment process is as follows: the strength of the electrode during corona is 20W·min / m 2 ~25W·min / m 2 .

Citation Information

Cited By

  • Preparation method of multi-layer co-extrusion composite insulating material

    CN120228981A

  • A method for preparing multi-layer co-extruded composite insulation material

    CN120228981B

  • Composite copper foil PP film with low melt index and high molecular weight

    CN120439628A